Primary Repair versus Reconstruction in Patients with Bilateral Anterior Cruciate Ligament Injuries: What Do Patients Prefer? - Harmen D. Vermeijden; Edoardo Monaco; Fabio Marzilli; Xiuyi A. Yang; Jelle P. van der List; Andrea Ferretti; Gregory S. DiFelice (Advances in Orthopedics)
Purpose. The purpose is to evaluate knee preference and functional outcomes of patients with primary anterior cruciate ligament (ACL) repair in one knee and ACL reconstruction in the contralateral side. Methods. All patients who underwent both procedures were retrospectively reviewed at minimum two-year follow-up. Patients were asked to complete questionnaires regarding their operated knees’ preferences during rehabilitation, daily activities, sports activities, and overall function. Furthermore, the Subjective International Knee Documentation Committee, Forgotten Joint Score-12, and Anterior Cruciate Ligament-Return to Sport after Injury were completed. Results. Twenty-one patients were included. All patients underwent ACL reconstruction first, which was displayed at younger age at surgery (24 vs. 33 years, p=0.010) and longer follow-up (10.2 vs. 2.3 years, p<0.001), respectively. Thirty-three percent preferred the repaired knee, 11% the reconstructed knee, and 56% had no preference; however, 78% indicated that their repaired knee was less painful during rehabilitation and 83% reported earlier range of motion (ROM) return following repair, which was similar for both knees in 17%. Eighty-three percent of patients indicated better function and progression during rehabilitation with their repaired knee and 11% with their reconstructed knees. No statistical differences were found in patient-reported outcomes between both procedures (all p>0.4). Objective laxity assessment showed mean side-to-side difference of 0.6 mm between both sides in favor of the reconstructed knee. Conclusion. This study showed that ACL repair and ACL reconstruction lead to similar functional outcomes. However, patients undergoing both procedures may have less pain, earlier ROM return, and faster rehabilitation progression following primary repair.